Earnings quality, cash flow and accruals persistence from others perspectives: Empirical evidence from U.S firms - Nga Thi Ngoc, Phan (2012)
The research aims to study the behavior and determinants of earnings quality and accruals persistence, examining the impact of both internal factor (components of earnings and accruals) and external factor (sign of income, economic state and business cycle). The main conclusion emerging from my study can be summarized Supporting Sloan’s conjectures; I find that persistence of earnings is higher than cash flow in high accruals firms but lower than cash flow in low accruals firms. And both extreme positive cash flow and negative cash flow reduce persistence of cash flow and earnings. Interestingly, even though the positive relationship between cash flow and earnings is strongly significant in my study, the result fails to show that accruals is negative correlated with earnings, which is commonly predicted in both theory and empirical evidence. Also empirical result reveals that accruals anomaly and cash flow anomaly do not necessarily occur together. Additionally, there is no significant difference on earnings persistence between firms reporting profit or loss, but earnings quality and accruals persistence do show negative impact from recession. Also the correlation between two components of earnings shows reversal during recession. Generally, my study supports the existence of accruals anomaly and earnings management, however we suggest that it is accruals that firms use in manipulation activities.